Increased Expression of Visfatin in Monocytes and Macrophages in Male Acute Myocardial Infarction Patients - Cheng-An Chiu; Teng-Hung Yu; Wei-Chin Hung; Li-Fen Lu; Fu-Mei Chung; I-Ting Tsai; Chih-Ying Yang; Chia-Chang Hsu; Yung-Chuan Lu; Jer-Yiing Houng; Yau-Jiunn Lee; Chao-Ping Wang (Mediators of Inflammation)
We demonstrated that visfatin expressed in monocytes and neutrophils and increased their reactivity in male acute ST-segment elevation myocardial infarction patients. Furthermore, visfatin was strongly appeared in lipid rich coronary rupture plaques and macrophages. These results suggest another explanation about leukocytes mediated visfatin that may play a pathogenesis role in coronary vulnerable plaques rupture.